Factors influencing nutritional literacy among rural older adults: a cross-sectional survey based on the theory of planned behavior - Liu, Shasha; Fan, Xiaomei; Jiang, Li; Liu, Tao (Frontiers in Nutrition, 2025)
ObjectiveTo investigate the factors influencing nutritional literacy among rural elderly individuals in northern Sichuan based on the theory of planned behavior (TPB).MethodsA convenience sampling method was employed to recruit 311 elderly participants (aged ≥60 years) from Sanlin Village (Cangxi County, Guangyuan City), Puji Village (Yilong County, Nanchong City), and Luhua Village (Bazhou District, Bazhong City). The survey instruments included general demographic questionnaires, the nutrition attitude scale (NAS), the multidimensional scale of perceived social support (MSPSS), the instrumental activities of daily living scale (IADLS), the general self-efficacy scale (GSES), and the nutrition literacy questionnaire for the Chinese elderly (NLQ-E). Data were analyzed using SPSS 26.0 and AMOS 23.0.ResultsHierarchical regression analysis revealed that education level positively predicted nutritional literacy (β = 0.126, t = 2.659, P < 0.01), while denture use due to tooth damage negatively predicted nutritional literacy (β = −0.077, t = −2.375, P < 0.05). Nutrition attitude (β = 0.312, t = 6.662, P < 0.001) and perceived social support (β = 0.243, t = 4.283, P < 0.001) were positive predictors, whereas daily living ability exhibited a negative predictive effect (β = −0.251, t = −4.445, P < 0.001). Structural equation modeling (SEM) indicated that nutrition attitude had a direct effect of 0.333 and an indirect effect of 0.050 on nutritional literacy. Daily living ability showed a direct effect of −0.481 and an indirect effect of −0.101. Self-efficacy partially mediated the relationships between nutrition attitude and nutritional literacy, as well as between daily living ability and nutritional literacy.ConclusionElderly individuals in northern Sichuan with more positive nutrition attitudes, higher perceived social support, and stronger daily living abilities demonstrated higher nutritional literacy. Self-efficacy partially mediated the influence of nutrition attitude and daily living ability on nutritional literacy.